Silver Nanoparticles: Synthesis, Characterization and their Application as a Sustainable Catalyst for Organic Transformations - A. Bhosale, Manohar; M. Bhanage, Bhalchandra (Current Organic Chemistry, 2015)
Size and shape selective syntheses of nanoparticles and their catalytic applications are gaining considerable interest in the recent years. Homogeneous catalysis is important due to its inherent advantages like mild reaction conditions and high selectivity. However, it suffers with serious drawback of catalyst-product separation and recycles as compared to their heterogeneous counterparts restricting their applications. The use of catalyst in the form of nano-size is an alternative methodology for combination of advantages of heterogeneous and homogeneous catalysis. Silver nanoparticles are important as they find applications in catalysis, organic transformations, synthesis of fine chemicals and organic intermediates. This review covers an overview of the synthesis of Ag nanoparticles, supported Ag nanoparticles and bimetallic Ag-metal nanoparticles and their characterization by various techniques. The applications of Ag nanoparticles in several organic transformations including C-C, C-N, C-S, C-O bond formation reactions as well as reduction and oxidation reactions are also discussed. The use of Ag nanoparticles in catalysis is advantageous as it avoids the use of ligands; easy separation of catalyst for recyclability makes the protocol heterogeneous and economic. Ag nanoparticles gave good catalytic activity towards desired products due to high surface area. By considering these advantages, researchers have focused their attention towards applications of Ag nanoparticles in catalysis.
Keywords: organic reaction